ANALISIS KEBIJAKAN PENINGKATAN KUALITAS SUMBER DAYA MANUSIA, DISIPLIN KERJA DAN PENGEMBANGAN KARIR PEGAWAI DI DINAS PERHUBUNGAN KABUPATEN NABIRE - Alfius Douw; Nur Aedah (JURNAL KEBIJAKAN PUBLIK, 2021)
This study aims to describe and analyze policies to improve the quality of Human Resources, work discipline, and career development at the Nabire Regency Transportation Service, as well as examine the factors that support and hinder their implementation. This research is a qualitative descriptive study. The location of the research is the Department of Transportation of Nabire Regency with the consideration of the accessibility of the researcher. The data collection techniques used are interviews and observation. Informants were selected purposively. The research instrument used was an interview guide and a recording device. Data analysis includes data preparation, data processing, data coding, data description, and data interpretation. The results showed that the policy of improving the quality of human resources was carried out by increasing soft skills (skills) by including Education and Training & Bimtek and hard skills (knowledge) by encouraging continuing higher education; implementing an online attendance system to monitor the punctuality of work, as well as the implementation of cutting performance allowances for employees who are often undisciplined; implementation of promotion and selection of open positions for personnel career development with indicators of employee performance appraisal and education level. The supporting factors are the institution's commitment to facilitating personnel to increase knowledge and skills, work discipline supported by a monitoring and evaluation system of employee work discipline, and career development with institutional commitment that fairly provides opportunities for all personnel to develop careers. The inhibiting factors are the willingness of employees to move forward to develop their quality, lack of socialization regarding Education and Training and Technical Guidance, lack of budget and quotas in training implementation, lack of personnel awareness regarding work discipline, and lack of existing personnel initiatives to develop their careers.